2009
DOI: 10.1016/j.cellbi.2009.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Chronological expression of Wnt target genes Ccnd1, Myc, Cdkn1a, Tfrc, Plf1 and Ramp3

Abstract: The canonical Wnt pathway regulates several biological processes including development, cell growth and proliferation via consecutive gene regulation. A high number of target genes of the Wnt pathway has been identified, but the chronological order of target gene expression is still elusive. This order is supposed to be crucial for the controlled course of events downstream of the activated Wnt pathway. Here we present the expression chronologies of the target genes Ccnd1 (encoding for cyclin D1), Myc (c-Myc),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 36 publications
3
31
0
Order By: Relevance
“…Ramp3 was found to be significantly similar to Tfrc and Tf in GRAIL analysis. Ramp3 and Tfrc are both known to be Wnt target genes (57). Several other genes located in identified putative QTL belong to Wnt pathway: Ankrd6 on Chromosome 4, Hnf1a on Chromosome 5 and Apc on Chromosome 18.…”
Section: Comparison Of Qtl Regions Associated With Liver Iron Levels mentioning
confidence: 99%
“…Ramp3 was found to be significantly similar to Tfrc and Tf in GRAIL analysis. Ramp3 and Tfrc are both known to be Wnt target genes (57). Several other genes located in identified putative QTL belong to Wnt pathway: Ankrd6 on Chromosome 4, Hnf1a on Chromosome 5 and Apc on Chromosome 18.…”
Section: Comparison Of Qtl Regions Associated With Liver Iron Levels mentioning
confidence: 99%
“…7A), each of which has been implicated in NSC self-renewal (Nakamura et al, 2000;Ohtsuka et al, 2001;Molofsky et al, 2003). By contrast, expression of c-Myc, a common target of the WNT pathway (He et al, 1998;Rohrs et al, 2009), was elevated in NSCs isolated from G-Cat mice (Fig. 7A).…”
Section: Research Articlementioning
confidence: 99%
“…Recently, another TfR-like molecule named TfR2 has been recognized and investigated (11,12), but the exact function of TfR2 remains unclear (8). It has been reported that the expression of TfR1 in mammary epithelial cells exhibits a significant 24-hour rhythm (13). Such rhythmic variation in TfR1 expression seems to affect its iron uptake function resulting in time-dependent changes in the internalization of iron-loaded Tf.…”
Section: Introductionmentioning
confidence: 99%